Freshwater Dinoflagellates of North America - Carty, Susan, 1948- (Book collections on Project MUSE., 2014)
Dinoflagellates are common unicellular organisms found in all types of aquatic ecosystems and are important contributors to freshwater ecosystems as significant primary producers of biomass. Despite increasing interest in the biology of living and fossil dinoflagellates, there has been no compilation of dinoflagellate species found in North America since 1934, and no keys to species. In Freshwater Dinoflagellates of North America, Susan Carty provides a much-needed taxonomic guide covering Canada, the United States, Mexico, all of Central America, the Caribbean, and Greenland. Features of the book include: " identification of dinoflagellate species, " distribution maps of species, " ecological and morphological keys to genera, " key to species within genus, " lists of references by location, " glossary, and " an extensive illustration program. Following an introductory section on the biology, morphology, and ecology of freshwater dinoflagellates, the species are presented in a field guide format with distribution maps, written descriptions emphasizing notable features, line drawings, and black-and-white and color micrographs